IMPLEMENTATION OF PANCAWASKITA COUNSELING IN STRENGTHENING STUDENTS' CHARACTER IN THE ERA OF DISRUPTION - Salsabiela, Najwa; Susanto, Adianna Muthia; Kurnianto, Yovityo Azitya; Habsy, Bakhrudin All (PT Altin Riset Publishing, 2025)
This study aims to empirically examine the implementation of Pancawaskita Counseling in strengthening the character of students in the era of disruption, by emphasizing the dimensions of responsibility, discipline, empathy, integrity, creativity, and other Pancasila values. Pancawaskita Counseling is considered relevant because it not only focuses on solving individual problems but also emphasizes the development of moral, spiritual, and social awareness in accordance with the Indonesian cultural context. The research used a qualitative approach with a case study method. Research informants include counseling guidance teachers, students as counselees, and related school parties. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis techniques with data reduction, data presentation, and conclusion drawing stages. The results showed that Pancawaskita Counseling can strengthen the internalization of the main character of students in facing the challenges of the digital era, including in terms of technology use and interaction in the digital cultural space. Supporting factors for implementation include the role of counseling teachers as facilitators, the openness of learners, and external support from families and communities. This research contributes to the development of a Pancasila value-based counseling model that is contextual to the needs of learners in the era of disruption.